Street Gang Hubbard Street Dance Chicago reviewed - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2002)
Review of Hubbard Street Dance Chicago. PALABRAS CLAVE: Hubbard Street Dance Chicago, Lou Conte, jazz dance, The Envelope, Queens / Black Milk.